2019
DOI: 10.1200/jop.18.00614
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Emergency Department Visits and Select Predictors of Hospitalization for Adults With Newly Diagnosed Cancer in a Safety-Net Health System

Abstract: PURPOSE: There is little description of emergency department (ED) visits and subsequent hospitalizations among a safety-net cancer population. We characterized patterns of ED visits and explored nonclinical predictors of subsequent hospitalization, including time of ED arrival. PATIENTS AND METHODS: This was a retrospective cohort study of patients with cancer (excluding leukemia and nonmelanoma skin cancer) between 2012 and 2016 at a large county urban safety-net health system. We identified ED visits occurri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 29 publications
(32 reference statements)
3
25
0
Order By: Relevance
“…Patients with cancer are more likely to be admitted to a progressive care or intensive care unit (11%) compared to the general population (2%) [9,10]. Between 34 and 49% are discharged home [8,10,17] and approximately, 4-5% of the remaining patients are transferred to another facility, die during the ED visits, or leave before physican evaluation or against medical advice [10,48].…”
Section: Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with cancer are more likely to be admitted to a progressive care or intensive care unit (11%) compared to the general population (2%) [9,10]. Between 34 and 49% are discharged home [8,10,17] and approximately, 4-5% of the remaining patients are transferred to another facility, die during the ED visits, or leave before physican evaluation or against medical advice [10,48].…”
Section: Estimatesmentioning
confidence: 99%
“…A potential explanation of the underuse of these phone-based triage resources is suggested by qualitative work finding that patients feel guilty for bothering providers [27]. While a common explanation of non-urgent ED use is that other outpatient alternatives were closed, at least two population-based US studies have found that roughly half of ED arrivals occur during business hours [38,48].…”
Section: Health System Factorsmentioning
confidence: 99%
“…This is similar to findings from other countries. [12][13][14] Management plans for all these symptoms can be initiated and instituted at EDs, especially for haemodynamically stable patients, and can potentially be relieved within several hours. ED observations units would have the resources to manage such complaints.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several international studies have described characteristics of cancer-related acute healthcare use, with infections and poorly controlled symptoms being key drivers of ED visits and subsequent hospital admissions. [11][12][13][14] In Singapore, limited…”
Section: Introductionmentioning
confidence: 99%
“…These toxicities commonly lead to high healthcare utilization, including frequent emergency department (ED) visits and prolonged hospitalizations, which contribute to the rising costs of cancer care, impaired patient quality of life (QOL), and morbidity related to treatment [ 1 16 ]. Notably, patients with advanced cancer experience multiple ED visits during the first year of diagnosis, with over half of these visits resulting in an inpatient hospitalization [ 4 6 , 17 ]. Moreover, over 40% of hospitalized patients with advanced cancer have a hospital readmission within 90 days of discharge and a substantial proportion of these hospitalizations are potentially avoidable [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%